2021
DOI: 10.3390/catal11121500
|View full text |Cite
|
Sign up to set email alerts
|

Defective Grey TiO2 with Minuscule Anatase–Rutile Heterophase Junctions for Hydroxyl Radicals Formation in a Visible Light-Triggered Photocatalysis

Abstract: The novelty of this work was to prepare a series of defect-rich colored TiO2 nanostructures, using a peroxo solvothermal-assisted, high-pressure nitrogenation method. Among these solids, certain TiO2 materials possessed a trace quantity of anatase–rutile heterojunctions, which are beneficial in obtaining high reaction rates in photocatalytic reactions. In addition, high surface area (above 100 m2/g), even when utilizing a high calcination temperature (500 °C), and absorption of light at higher wavelengths, due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 54 publications
(68 reference statements)
2
6
0
Order By: Relevance
“…BET analysis estimated the surface areas of prepared TiO2 and Cu-TiO2 to be 52.1 a 9.9 m 2 /g, respectively (Figure 3). It can be related to changes in the morphology and cr talline structure of the TiO2 after doping with Cu [30]. This result agreed with Tasbih al.…”
Section: Characterization Of As-prepared Tio 2 and Cu-tiosupporting
confidence: 90%
See 3 more Smart Citations
“…BET analysis estimated the surface areas of prepared TiO2 and Cu-TiO2 to be 52.1 a 9.9 m 2 /g, respectively (Figure 3). It can be related to changes in the morphology and cr talline structure of the TiO2 after doping with Cu [30]. This result agreed with Tasbih al.…”
Section: Characterization Of As-prepared Tio 2 and Cu-tiosupporting
confidence: 90%
“…talline structure of the TiO2 after doping with Cu [30]. This result agreed with Tasbihi et al [34] and Bensouici et al [22], who reported a decrease in the surface area of TiO2 after doping with Cu.…”
Section: Characterization Of As-prepared Tio 2 and Cu-tiosupporting
confidence: 88%
See 2 more Smart Citations
“…Anatase TiO 2 is an indirect bandgap semiconductor, and electrons in the conduction band need to undergo a shift to recombine with holes in the valence band, which inhibits the recombination of electron-hole pairs and thus has high photocatalytic activity. Moreover, In order to obtain photocatalysts that can have better light absorption, the materials can be treated by other means such as hydrogenation or doping, while their color changes to black, [29][30][31][32] blue, [33,34] brown, [35][36][37] red, [38,39] yellow, [40,41] grey, [42][43][44] etc.…”
Section: Structural Characteristics Of Tiomentioning
confidence: 99%